تحقیق و تخریج ِ احادیث کے ضمن میں روایات حضرت ام سلمہ کا تجزیاتی مطالعہ: A critical study of the narrations of Hazrat Umm e Salama in the context of Research and Authentication of Hadiths - Iftikhar Ahmad; Muhammad Fiaz Ud Din; Shabnam Begum (Al Manhal Research Journal, 2023)
Looking at the narrations of Hazrat Umm e Salama R.A, it becomes evident that Divine has entrusted her with the task of promoting and teaching the sayings of the Prophet Muhammad (peace be upon him) among the important duties of life. Particularly, those significant corners of the life of the Prophet (peace be upon him) which no one else could explained with such clarity. No one else could possess the knowledge, teachings, guidance, and principles for the guidance of humanity, especially when it comes to the personal and family life. For the best guidance of the Ummah (community), Hazrat Umm e Salama (may Allah be pleased with her) saw, heard, and learned from the Prophet Muhammad (peace be upon him) as a life partner. As time passed, the systematic collection of Hadiths began, and the purpose was to preserve the Hadiths. The narratives of Umm e Salama are a significant part of this collection. Most of this collection is related to the personal and domestic life of the Noble Prophet (peace be upon him), and it is also necessary to present it with sensitivity. Below, attention is given to these matters.